Nanoporous Superhydrophobic Coatings that Promote the Extended Release of Water-Labile Quorum Sensing Inhibitors and Enable Long-Term Modulation of Quorum Sensing in Staphylococcus aureus - Kratochvil, Michael J. (ACS Biomater Sci Eng, 2015)
[Image: see text] Materials and coatings that inhibit bacterial colonization are of interest in a broad range of biomedical, environmental, and industrial applications. In view of the rapid increase in bacterial resistance to conventional antibiotics, the development of new strategies that target nonessential pathways in bacterial pathogens—and that thereby limit growth and reduce virulence through nonbiocidal means—has attracted considerable attention. Bacterial quorum sensing (QS) represents one such target, and is intimately connected to virulence in many human pathogens. Here, we demonstrate that the properties of nanoporous, polymer-based superhydrophobic coatings can be exploited to host and subsequently sustain the extended release of potent and water-labile peptide-based inhibitors of QS (QSIs) in Staphylococcus aureus. Our results demonstrate that these peptidic QSIs can be released into surrounding media for periods of at least 8 months, and that they strongly inhibit agr-based QS in S. aureus for at least 40 days. These results also suggest that these extremely nonwetting coatings can confer protection against the rapid hydrolysis of these water-labile peptides, thereby extending their useful lifetimes. Finally, we demonstrate that these peptide-loaded superhydrophobic coatings can strongly modulate the QS-controlled formation of biofilm in wild-type S. aureus. These nanoporous superhydrophobic films provide a new, useful, and nonbiocidal approach to the design of coatings that attenuate bacterial virulence. This approach has the potential to be general, and could prove suitable for the encapsulation, protection, and release of other classes of water-sensitive agents. We anticipate that the materials, strategies, and concepts reported here will enable new approaches to the long-term attenuation of QS and associated bacterial phenotypes in a range of basic research and applied contexts.